Influences of Floater Motion on Gap Resonance Triggered by Focused Wave Groups - Gao, Jun-liang; Lyu, Jing; Zhang, Jian; Zang, Jun (China ocean engineering, 2023)
The current study investigates the hydrodynamic characteristics of gap resonance within a narrow gap formed by two adjacent boxes subjected to incident focused transient wave groups. A two-dimensional (2D) numerical wave tank based on the OpenFOAM package is utilized for this purpose. The weather-side box is fixed while the lee-side box is allowed to heave freely under wave actions. The effects of the focused wave amplitude and spectral peak period on the wave amplification within the gap, motion of the lee-side box, and wave forces (including horizontal and vertical wave forces) acting on each box are systematically examined. For comparison, another structural layout consisting of two fixed boxes is also considered. The results reveal that the release of the heave degree of freedom (DoF) of the leeside box results in remarkably distinct resonance features. In the heave-box system, both its fluid resonant period and the period corresponding to the maximum heave displacement of the lee-side box are significantly larger (i.e., 1.6–1.7 times) than the fluid resonant period of the fixed-box system. However, the wave amplification factor inside the gap in the heave-box system is significantly lower than that in the fixed-box one. Both the variations of the maximum horizontal and vertical wave forces with the spectral peak period and their magnitudes are also significantly different between the two structural systems.